Indenture in Language: The Words the Workers Made - Mesthrie, Rajend (The Journal of Natal and Zulu history, 2021)
This paper affords an overview of the linguistic resources that indentured labourers (1860-1911) brought with them from different parts of India, as well as of the linguistic adaptations evident in the South African forms of Tamil, Bhojpuri-Hindi, Urdu and Telugu. These changes pertain to the coalescence of different but closely related Indian dialects to form distinct plantation varieties of each of these, as well as to the adoption of words from each other and other languages of South Africa (Afrikaans, English, Zulu). Although Indian languages are no longer widely spoken, it is argued that documentation of their resources and the resourcefulness of their speakers is an important sociolinguistic and historical activity. Furthermore, some of the words have consciously and sometimes unwittingly passed into the colloquial English of Indian communities in KwaZulu-Natal.